2012
DOI: 10.1186/1475-2891-11-4
|View full text |Cite
|
Sign up to set email alerts
|

Wild bitter gourd improves metabolic syndrome: A preliminary dietary supplementation trial

Abstract: BackgroundBitter gourd (Momordica charantia L.) is a common tropical vegetable that has been used in traditional or folk medicine to treat diabetes. Wild bitter gourd (WBG) ameliorated metabolic syndrome (MetS) in animal models. We aimed to preliminarily evaluate the effect of WBG supplementation on MetS in Taiwanese adults.MethodsA preliminary open-label uncontrolled supplementation trial was conducted in eligible fulfilled the diagnosis of MetS from May 2008 to April 2009. A total of 42 eligible (21 men and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(43 citation statements)
references
References 37 publications
1
40
1
1
Order By: Relevance
“…Recent studies have demonstrated that wild bitter gourd extracts exhibited multiple pharmacological activities associated with anti-inflammation and antidiabetics, including those of suppressing inflammatory response in macrophages [7], overcoming insulin resistance in skeletal muscle in fructose-fed rats [8], enhancing insulin signaling in skeletal muscle in high-fat-diet-fed mice [9], and upregulating mRNA expression of peroxisome proliferator-activated receptor (PPAR) α , PPAR γ , and their target genes in mice [10]. Together, these activities might account for the ability of wild bitter gourd to improve metabolic syndrome in humans [11]. …”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have demonstrated that wild bitter gourd extracts exhibited multiple pharmacological activities associated with anti-inflammation and antidiabetics, including those of suppressing inflammatory response in macrophages [7], overcoming insulin resistance in skeletal muscle in fructose-fed rats [8], enhancing insulin signaling in skeletal muscle in high-fat-diet-fed mice [9], and upregulating mRNA expression of peroxisome proliferator-activated receptor (PPAR) α , PPAR γ , and their target genes in mice [10]. Together, these activities might account for the ability of wild bitter gourd to improve metabolic syndrome in humans [11]. …”
Section: Introductionmentioning
confidence: 99%
“…We previously reported that BG extracts can activate and upregulate the expressions of peroxisome proliferator-activated receptors (PPARs) and identified 9c, 11t, 13t-conjugated linolenic acid as one of the active components [38, 39]. In a preliminary clinical study with 42 metabolic syndrome subjects, the incidence of metabolic syndrome and waist circumference was significantly decreased after a supplementation of 4.8 g/d of lyophilized wild bitter gourd powder (BGP) for 3 months [40]. …”
Section: Introductionmentioning
confidence: 99%
“…It increases sensitivity of the insulin receptor [17], reduces insulin resistance and hyperinsulinemia, with favourably influence on the metabolic syndrome [18] and diabetes [19] in humans. Obesity promotes prostate cancer [20] which has been related to hyperinsulinemia and insulin resistance [2,[21][22][23].…”
Section: Discussionmentioning
confidence: 99%